An Unusual Case Report on Co-Morbidity with Sexual Assault in the Mthatha Hospital, South Africa - B Meel (Institute of Medico-legal Publications Pvt Ltd, 2022)
Background: Comorbidity or the co-occurrence of mental disorders and substance abuse disorders is common among victims of sexual assault. Occasionally life-threatening conditions have been observed in these patients which need immediate medical attention. Objective: To highlight the unusual case report of co-morbidity with sexual assault in a rural hospital in South Africa. Case History: A seven-year-old girl was referred from a health center to a rural hospital with a history of sexual assault over four days by an unknown man. She was threatened to be killed in the case of disclosure. Her aunt suspected that she had a problem as she was not walking normally. Then she opened and described the whole incident. She was having a history of vaginal discharge with vomiting and diarrhea along with mild fever. She was also depressed. On physical examination, genital injuries including a ruptured hymen were confirmed. She was having muscle guarding of abdominal muscles. The victim was refused admittance as she was labeled a case of rape, but after persistent persuasion of the staff, she was admitted and later operated on for acute appendicitis. This case history, her physical examination, and the difficulty in getting admission to a surgical ward are discussed in this report. Conclusion: Sexual assault may be associated with co-morbidity like acute appendicitis. Doctors must be vigilant in identifying such life-threatening co-morbidity to save the life of a patient.